2018
DOI: 10.3390/ijms19103092
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Modulation of AMPK-Impact upon Metabolic-Inflammation

Abstract: Nutritional status provides metabolic substrates to activate AMP-Activated Protein Kinase (AMPK), the energy sensor that regulates metabolism. Recent evidence has demonstrated that AMPK has wider functions with respect to regulating immune cell metabolism and function. One such example is the regulatory role that AMPK has on NLRP3-inlflammasome and IL-1β biology. This in turn can result in subsequent negative downstream effects on glucose, lipid and insulin metabolism. Nutrient stress in the form of obesity ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 99 publications
3
82
2
1
Order By: Relevance
“…AMPK is one of the most important energy sensors identified so far that can regulate the cellular metabolism. Similarly, AMPK inhibits a broad range of inflammatory reactions through multiple biological pathways by regulating immune cell metabolism and functions (41,42). In our current study, no obvious differences in the serum levels of AMPK-α1 and p-AMPK-α1 between OA and RA patients were observed.…”
Section: Discussioncontrasting
confidence: 46%
“…AMPK is one of the most important energy sensors identified so far that can regulate the cellular metabolism. Similarly, AMPK inhibits a broad range of inflammatory reactions through multiple biological pathways by regulating immune cell metabolism and functions (41,42). In our current study, no obvious differences in the serum levels of AMPK-α1 and p-AMPK-α1 between OA and RA patients were observed.…”
Section: Discussioncontrasting
confidence: 46%
“…Another therapeutic target for obesity could be AMPK, a signaling protein involved in adapting cellular metabolism in response to nutritional variations. [30] Previous in vitro studies with 3T3-L1-adipocytes have shown a beneficial effect of Lippia citriodora polyphenols on decreasing triglyceride accumulation and reducing ROS generation, which was linked to AMPK modulation. [24] In the present study, HFD-fed mice showed a reduced expression of Ampk in the adipose tissue, which was but completely restored by LCE treatment (Figure 2B).…”
Section: Effects Of Lce On Inflammatory Status and Gut Dysbiosismentioning
confidence: 99%
“…More recently, the treatment of db/db mice with an activator of adiponectin, AdipoRon, showed the upregulation of phosphorylated AMPK in the kidney along with reduced inflammation and lipotoxicity [30]. Finally, obesity and diabetes are associated with inflammation and oxidative stress that are both recognized to inhibit AMPK [61]. The pro-inflammatory cytokine TNFα is known to suppress AMPK activity via the induction of protein phosphatase 2C (PP2C) in skeletal muscle in vitro and in vivo, suppressing fatty acid (FA) oxidation and promoting insulin resistance [62].…”
Section: Ampk Activity In Obesity and Diabetes-induced Chronic Kidneymentioning
confidence: 99%